2022
DOI: 10.1111/cwe.12411
|View full text |Cite
|
Sign up to set email alerts
|

Does Bank Competition Promote Corporate Green Innovation? Evidence from the Location of Bank Branches

Abstract: Based on the geographic coordinates of bank branches and firms, this study analyzes the impact of firm‐level bank competition on corporate green innovation and its underlying mechanisms. The findings of this study are mainly as follows. First, bank competition promotes corporate green innovation by reducing transaction costs, increasing the possibility and quantity of firms applying for green patents. Second, bank competition increases the share of green innovation while reducing the share of nongreen innovati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…Xin et al [ 19 ] find that bank deregulation on city commercial banks in China has significantly positive effect on firm innovation. Additionally, Xia and Liu [ 36 ] explore the impact of bank competition on firm green innovation in China. Tan et al [ 37 ] illustrate that a combination of industry and finance serves as a moderating factor in the relationship between bank competition and enterprise innovation.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Xin et al [ 19 ] find that bank deregulation on city commercial banks in China has significantly positive effect on firm innovation. Additionally, Xia and Liu [ 36 ] explore the impact of bank competition on firm green innovation in China. Tan et al [ 37 ] illustrate that a combination of industry and finance serves as a moderating factor in the relationship between bank competition and enterprise innovation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Following the literature [ 36 , 44 ], we control for firms’ size ( Size ), age ( lage ), return on assets ( ROA ), firms’ leverage ( leverage ) and whether a firm is an export firm ( export ). To mitigate the omitted variable bias, we also control the GDP per capita ( lgdppc ), bank density ( Bankdens ), the government expenditure on science and technology ( lnSTexp ), and the employee wages ( lnWage ) in a city.…”
Section: Sample Measures and Summary Statisticsmentioning
confidence: 99%
“…This section analyzes how a policy can encourage enterprises to increase their R&D investment. Cost is an important factor influencing corporate innovation (Xia and Liu, 2022). Super-deductions of R&D expenses inevitably reduce the cost of R&D investment and increase net cash flow.…”
Section: Mechanism Analysismentioning
confidence: 99%
“…Banks can also reduce loan interest rates and relax loan conditions, effectively easing financing constraints (Beck & Demirguc-Kunt, 2006). Xia and Liu (2022) showed that the competitive bank environment faced by enterprises based on geographical distance can promote green innovation.…”
Section: Access To Credit and Green Innovationmentioning
confidence: 99%